2020
DOI: 10.1037/ort0000455
|View full text |Cite
|
Sign up to set email alerts
|

Mental health, minority stress, and the Australian Marriage Law postal survey: A longitudinal study.

Abstract: Research indicates that marriage equality legislation is associated with improved mental health outcomes for lesbian, gay, bisexual, transgender, and queer (LGBTQ) people. However, the public debate that often precedes such legislation may exacerbate psychological distress and minority stress. In 2017, the Australian Federal Government conducted a national survey to gauge support for marriage equality. The present study investigated the mental health of a sample of LGBTQ people during and after this survey per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Meanwhile, the period preceding the enactment of SSM legislation was also marked by heated debate and a proliferation of opposing opinions and anti-gay comments. These social dynamics could have provoked emotions among members of LGB communities [ 38 , 39 ]. The post-legalization data were collected during the COVID-19 pandemic that has imposed a collective influence on citizens’ mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the period preceding the enactment of SSM legislation was also marked by heated debate and a proliferation of opposing opinions and anti-gay comments. These social dynamics could have provoked emotions among members of LGB communities [ 38 , 39 ]. The post-legalization data were collected during the COVID-19 pandemic that has imposed a collective influence on citizens’ mental health.…”
Section: Discussionmentioning
confidence: 99%
“…The period directly after the 2017 Australian Marriage Law Postal Survey was particularly difficult for many LGBT+ people. Multiple studies have demonstrated that the public debate heightened levels of psychological distress and fear among LGBT+ people (Casey et al, 2020; Ecker et al, 2019; Richardson‐Self et al, 2018; Verrelli et al, 2019). This means that some LGBT+ workers we interviewed were particularly sensitised to issues of discrimination and prejudice in the workplace.…”
Section: Methodsmentioning
confidence: 99%
“…Citing concern for its impact on the psychological wellbeing of LGBTQ Australians, the Australian Psychological Society (2017) issued a statement opposing the postal survey. Subsequent cross-sectional (Bartos et al, 2020; Ecker et al, 2019; Verrelli et al, 2019) and longitudinal (Casey et al, 2020) research found that heightened symptoms of depression, anxiety, and stress were indeed reported by LGBTQ Australians during the postal survey period.…”
Section: Theoretical Frameworkmentioning
confidence: 99%